PENGARUH PETUNJUK UNTUK BERTINDAK PADA IBU TERHADAP KELENGKAPAN IMUNISASI DASAR ANAK - Lintang Pratiwi Utviaputri (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2018)
The moment children are born into the world, they are in a vulnerable condition. A complete basic child immunization as a preventive measure to protect them from a threat such as transmission of deadly disease is required. A mother, as the closest figure close to the children in everyday life, is considered as an important subject that will actively to complete the basic immunization to their children. To determine the act of giving immunization, a mother will be affected by several factors, an external influence for example. To understand the external influence that could affect the mother’s action, Health Belief Model (HBM) theory can be used, where the external influence is called cues to action. This study was conducted to determine the influence of cues to action on the mother to complete basic child immunization to their children. The research was executed by a cross sectional study with quantitative approach. The subject are consisted from 40 mothers as the research respondents with the following condition; having children between age 1 to 2 years old. The subject has been selected from a number of population that has been determined by simple random sampling method. The instrument used in this study is a questionnaire and conducted via interview. Based on the results from the interview, it can be found that both complete and incomplete condition in terms of completeness of immunization are 50%-50%. The test is followed by comparing the conditions of completeness of immunization with cues to action variable. The results is cues to action variable has a significant relationship to the completeness of child immunization with a significance value of 0.002 (p <0.05). It can be concluded that cues to action have an effect on mothers so that they are more willing to complete immunization on their child. Keyword: complete basic child immunization, mother, cues to action, health belief model